Self-Talk As a Regulatory Self-Confidence: A Descriptive Study of Athlete Long Jump - Maharani, Putri Maulidina; Sartono, Hadi; Kusumah, Widi; Mulyana, Mulyana (Indonesian Journal of Sport Management, 2024)
Mental aspects have a great influence on the overall development and growth of athletes, both in the training process and outside of training. Therefore, it must have a good psychological condition, especially self-confidence. Self-talk is one method of psychological training that is useful for various things, one of which is athlete self-confidence. This study aims to determine the relationship of self-talk to the confidence of long jump athletes. A quantitative descriptive method was used in this study using a correlation design. This study involved 6 Majalengka Regency long jump athletes as samples who were then given a questionnaire as a research instrument to measure self-confidence and self-talk. After the data was obtained, it was analyzed using SPSS version 25 using the correlation test. The results showed that there was a significant relationship between self-talk and self-confidence in long jump athletes. So it can be concluded that self-confidence and self-talk are two aspects that are equally important for athletes to have because they are closely related to one another.